2019
DOI: 10.1002/cbic.201900097
|View full text |Cite
|
Sign up to set email alerts
|

What Is the “Relevant” Amyloid β42 Concentration?

Abstract: Alzheimer's amyloid beta can perform a wide variety of actions that are highly concentration dependent. This viewpoint aims to provide a framework for basic considerations on what might be considered brain‐relevant concentrations of the peptide. Some implications for the therapeutic implementation of the recently emerged oligomer‐to‐fibril strategy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The conformational selection preference for the rippled interface might become most apparent at low concentrations, where the encounter probability between the Aβ peptides is reduced. This might be particularly important for in vivo application of oligomer‐to‐fibril conversion, where nanomolar concentrations of Aβ lead to synaptotoxicity …”
Section: Resultsmentioning
confidence: 99%
“…The conformational selection preference for the rippled interface might become most apparent at low concentrations, where the encounter probability between the Aβ peptides is reduced. This might be particularly important for in vivo application of oligomer‐to‐fibril conversion, where nanomolar concentrations of Aβ lead to synaptotoxicity …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that the concentrations of each Aβ alloform are substantially lower in the retina than in the brain, which is in accordance with previously published results in animal models and human donors (Alexandrov et al, 2011; Grimaldi et al, 2018; Koronyo et al, 2017; Koronyo‐Hamaoui et al, 2011; Schultz et al, 2020; Shi et al, 2020). Of note, it is believed that the concentrations of Aβ 42 deemed detrimental or toxic to brain cells and can lead to LTP deficits are dose‐dependent (Raskatov, 2019). Whether and how retinal concentrations translate to retinal cell toxicity and pathology warrant future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Early pathological changes in AD involve accumulation of amyloid β-protein (Aβ) in the brain and retina (5)(6)(7)(8)(9)(10)(11), with the amyloidogenic 42-residue long alloform (Aβ 42 ) viewed as the most pathognomonic (5,12). These Aβ 42 peptides have been shown to rapidly aggregate into insoluble fibrils that form the plaques in AD brains, but also to assemble into non-fibrillar soluble oligomers, believed to be highly neurotoxic (8,(13)(14)(15)(16)(17)(18)(19)(20). While there is a weak correlation between cerebral plaque density and severity of AD, Aβ 42 oligomers appear to closely associate with synaptopathy and cognitive impairment (21,22).…”
Section: Introductionmentioning
confidence: 99%